Placental Transport of Zidovudine in the Rhesus Monkey - Louis E. Ridgway III; Thomas S. King; George I. Henderson; Steven Schenker; Robert S. Schenken (Hindawi Limited, 1993)
Objective: This study was undertaken to characterize the pharmacokinetics of zidovudine (ZDV) and ZDV-glucuronide (ZDVG) in the material and:fetal circulations of the rhesus monkey.